Uso da somatotropina bovina recombinante - rbST como alternativa para a produção de leite de cabra na entressafra - Barbosa, Paula Galvano [UNESP]; Gonçalves, Heraldo Cesar [UNESP]; Wechsler, Francisco Stefano [UNESP]; De Resende, Kleber Tomás [UNESP]; Da Silva Sartori, Denise Rangel [UNESP]; De Pauli, Laís Fernanda Callado [UNESP]; Pulz, Lilian Martini [UNESP]; Losi, Tiago Creste [UNESP] (My University, 2002)
The experiment was conducted at the Goat Husbandry Sector of FMVZ - UNESP - Botucatu Campus, with the purpose of studying the influence of recombinant bovine somatotropin (rbST - commercial name: Boostin 250 mg) on the lactation curve, milk production, milk constituents, body weight and body score of goats during the lactation cycle. Twenty-one Alpine Brown goats between 1 1/2 and 4 years old were used, randomly allotted to three treatments with seven animals each: control (T1 - no rbST), complete (T2 - rbST after the milk production peak) and low production season (T3 - rbST during the low production season). All animals received the same diet, excepting the amount of concentrate, which was adjusted according to milk yield. No increase in milk yield was observed in the treated animals, but lactation persistency was greater in these goats. The body weight and the body score also did not show significant difference between treatment and control animals.
Use of recombinant bovine somatotropin - rbST as an alternative for lactating goats during the low production season
Keywords: Goats; Lactation curve; Persistency